2005
DOI: 10.1007/s11096-005-1636-x
|View full text |Cite
|
Sign up to set email alerts
|

Using Imipenem and Cilastatin During Continuous Renal Replacement Therapy

Abstract: The heterogeneity of the studies identified prevents them being analysed as a single group. For meaningful dosage recommendations to be made, further studies are required using larger populations and with more detail regarding liver dysfunction and duration of renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…This increase is in part due to the utilization of larger-surface-area hemofilters and higher ultrafiltration rates. The CVVHDF clearance of imipenem has generally been greater than that observed with CVVH; values have ranged from 18.7 to 57 ml/min, with higher values being observed in patients who had greater Q UFD rates (9,10,21).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This increase is in part due to the utilization of larger-surface-area hemofilters and higher ultrafiltration rates. The CVVHDF clearance of imipenem has generally been greater than that observed with CVVH; values have ranged from 18.7 to 57 ml/min, with higher values being observed in patients who had greater Q UFD rates (9,10,21).…”
Section: Discussionmentioning
confidence: 91%
“…The influences of CRRT on the removal of drugs have also been noted to be markedly variable, although there is a clear trend in the last 10 to 15 years toward higher clearances with all agents that have been evaluated throughout this time period (3,9,12,21). The clearances of imipenem by CVVH ranged from 6.5 to 13.3 ml/min in the 1990s and have increased to 22.9 to 36.0 ml/min during the last decade (9,10,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that insufficient information is obtained to permit extrapolation to another group of patients with other systems or haemodiafiltration dosage. This is particularly relevant for β-lactam antibiotics or azoles 16 17. This high variability of concentrations is largely due to changes in the patient with renal failure (including weight, plasma proteins and non-renal clearance of drugs)18 19 and the equipment used (haemofiltration system, flow or membrane used by the system) 5 20 21…”
Section: Discussionmentioning
confidence: 99%
“…Total clearances were higher than previously published (158.82 to 506.83 mL/ min) with membrane clearance ranging from 9% to 18%. [31] Ertapenem and doripenem The newer carbapenems ertapenem and doripenem are more stable after reconstitution and have a longer t1/2. Mistry et al showed that hemodialysis cleared approximately 30% of the ertapenem dose.…”
Section: Imipenemmentioning
confidence: 99%